“Minat, Motif, Tujuan, dan Manfaat Membaca Novel Teenlit Bagi Remaja Jakarta: Studi Resepsi Sastra” - Redyanto Noor (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The reality of young readers'(Jakarta) receptions of the teenlit novel concerning the motives, purposes, and benefits of reading the teenlit novel explains the social-cultural function of teenlit novel. Teenlit novel as a means of entertainment is able to fulfill the social-cultural function, which is giving spiritually pleasure, to be able to accommodate the horizon-expectations of adolescent readers. Teenlit novel provides entertainment while teaching "something" to teenagers. Teenlit novel serves as a social media such as self-identification, actualization, and socialization. Teenlit novel directly or indirectly has function to develop personality: independent, confident, and more mature. However, in some ways there is a contradictory reality between the motives, goals, and benefits of reading teenlit novels among teenagers. The contradictory reality is the absence of a correlation between motives and goals with the benefit of reading teenlit novel. The motive of spare time is not correlated with the purpose of gaining knowledge. The purpose of acquiring knowledge is not correlated with the benefits of not feeling smarter. These facts indicate that there are important issues relating to information and values promoted by the novel teenlit and the value system prevailing in adolescent social life.